Phytochemical Analysis and Biological Activity Test and Functional Group Detection of Eucalyptus Globulus - Gyawali, Hari; Ghimire, Albert; Dhital, Toran Dip (BMC Journal of Scientific Research, 2022)
This study was designed to explore phytochemical screening and antimicrobial activity of the Eucalyptus globulus. Extraction of phytochemical was performed by Soxhlet apparatus using ethanol and hot water extraction using water. The phytochemical screening of ethanolic extract showed the presence of alkaloids, carbohydrates, saponins, phenols, tannins, flavonoids, terpenoids, proteins & amino acids, steroids, volatile oils, and aqueous extract showed the presence of alkaloids, carbohydrates, glycosides, saponins, phenols, tannins, flavonoids, proteins & amino acids, gums and mucilage, and steroids. Agar well diffusion method was used for the antimicrobial activity test. Both ethanolic and aqueous extracts of E. globulus are resistant to the E. coli, Staphylococcus sp., and Bacillus species except ethanolic extract shows activeness against Staphylococcus sp. & Bacillus species. Both ethanolic and aqueous extracts of E. globulus show inactivity against Aspergillus species. This study concludes the phytochemicals derived from given plants has great potential to treat life-threatening disease. The FTIR studies show that plant extracts consist of amine, carboxylic acid, alcohol & nitro compounds as the most abundant component.